Revision of the Liverwort genus Asterella P. Beauv. (Marchantiales, Aytoniaceae) in Continental Eurasia, Malesia and Japan - Long, David Geoffrey (Trinity College (Dublin, Ireland). Department of Botany, 2001)
This study constitutes a taxonomic revision of the genus Asterella in Eurasia, Asterella belongs to the family Aytoniaceae in the Chambered Liverworts (Marchantiales). It is poorly understood taxonomically and a worldwide revision of the c. 158 described species is badly needed. Its gametophyte is morphologically complex and rich in qualitative characters; the sporophyte is highly reduced but shows great diversity in spore ornamentation patterns. Marchantiales are among the earliest land plants but relationships and phylogeny are poorly understood.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin